Does Corruption Perception Index Moderating The Tax Ratio Factors’s Determinants? - ali farhan (Universitas Islam Negeri Mataram, 2025)
This research aims to determine whether the Corruption Perception Index will significantly influence the determinant variables on the tax ratio as measured by GDP, Population, and Purchasing Power Parity. The analysis test in this research uses multiple linear regression through the EVIEWS program using sample panel data from ASEAN countries for the period 2012-2020. The analysis results show that GDP has a partial negative and significant effect on the tax ratio, Population has a positive and significant effect on the tax ratio, purchasing power parity has a negative and insignificant effect on the tax ratio, while CPI is indicated to moderate the influence of these three determinant variables on the tax ratio. From this research, it can be learned that to increase the tax ratio, the main thing that must be improved is improving state governance, so that public trust and awareness of paying taxes will also increase.